Adaptable Reuse and Restoration of Florya, Senlikkoy Old Church - Mosque - Sedes, Fatma (Architecture Image Studies, 2024)
The church, at Şenlikköy, (a small Rum village in the 1800’s), was built in the 1900’s. With the decrease of the Anatolian Rum population in years and even the extinction due to migration, the church was converted into a mosque as Muslim families settled in the village. It was used as a mosque in the oral history interviews with the elders and the headman (muhtar) of Şenlikköy. It was learned that a timber minaret was added to the structure, but no visual material could be obtained about it. Due to the decline or disappearance of the Christian community, minarets were added to some churches. Such Greek, Rum, and Armenian churches in Anatolia and some districts of Istanbul were converted into a mosques. It is mostly seen similar examples in Fatih District, İstanbul. Imrahor Mosque is the most well-known example of the basilica church type in Turkey (Church of Yoharines Studios). Over time Basilicas in Anatolia, a development has occurred that will affect the form. The best-known examples in Istanbul can be listed as follows: Acem Ağa Masjid (1484) (Chelkopratia Church) (5th century) Atik Mustafa Pasha Mosque (16th century) (St. Peter's Church) (11th century) Kefeli Masjid (1935) (St.Nikolaus Church) (16th century) Monastery Masjid (15th century) (Monastery Church) (11th century) Sekbanbaşı Masjid (15th century) (Name not known) (?) Sinan Pasha Masjid (16th century) (Red Church) (14th century) The political and religious aspects of the conversion of small-scale churches into mosques are not discussed in this report, it is not the subject. A new function as a library and cultural center is aimed to be given to this historic building as mentioned (FLORYA, SENLIKKOY OLD CHURCH / MOSQUE) with a revitalization project.